How uncertainty in industry policy affects corporate investment in China. (16th March 2022) - Deloof, Marc; Yang, Jie; Xu, Chaoyang
Abstract: In this paper, we investigate the link between uncertainty in industrial policy and firm investment by focusing on China's five‐year plan (FYP). Our sample period is from 1998 to 2017. In our investigation, we examine whether a change in the FYP is a source of uncertainty in industrial policy because of the difficulties in FYP predictability. Our main finding is that there are systematic decreases in investments in the year prior to a new FYP. The finding is robust to endogeneity. We also find that the relation between the uncertainty in industrial policy and investment is heterogeneous in the cross section. This heterogeneity is caused by information advantages about new FYP, dependence on government subsidies, investment irreversibility and industry competition. Further, investment rebounds after resolving the uncertainty but are dampened by adjustment costs.